Penggunaan Media Seesaw Class pada Kegiatan Belajar dari Rumah Selama Pandemi Covid-19 - Twiningsih, Anik (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2021)
The objective of the study is to describe the effectiveness of the media seesaw class in learning from home based in networks (online). This study applied descriptive qualitative research. Data collection techniques used were through interviews, observation, documentation and online portfolios. The subjects of this study were 3rd grade students of SD Negeri Laweyan, Surakarta. The results of this study prove that the media seesaw class has a positive impact on learning from home for students during the Covid-19 pandemic. This is shown by the various seesaw class features that make it easier for teachers and students to learn from home during the Covid-19 pandemic. The seesaw class application that can be accessed via Andorid's cellphone not only makes it easier for teachers and students to interact, but also interactions between students. This is what increases student learning activities at home because both teachers and students are not fixated on time